South Pole (SPICEcore) Borehole Deformation - Pettit, Erin (IEDA: US Antarctic Program Data Center, 2020)
Acoustic Televiewer measures borehole shape and tilt. These data were collected to study detailed borehole deformation with respect to ice properties to expand our understanding of the flow law for ice.